(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2023)
This article addresses the legal status of international human rights treaties in Brazil. To this end, from the analysis of the case concerning the requirement of a degree in journalism for the exercise of the profession, it deals with the relations between international law and the internal legal order, as well as the control of conventionality and the dialogue of the Courts. Thus, it presents a study of the Brazilian jurisprudential evolution in the application of international human rights treaties, from the promulgation of the Federal Constitution of 1988 to the present day, showing progress in the opening of the Brazilian Judiciary to the international system of human rights protection in recent decades. In order to conclude that, following this evolutionary line, it is possible to expect that the concomitant change in the national legal culture will lead to the future recognition of the constitutional character of all international human rights treaties, thus favoring the universal and special character of these rights, necessarily immune to modifications that mitigate them.